Ribosomal PCR and DNA sequencing for detection and identification of bacteria: experience from 6 years of routine analyses of patient samples. Issue 3 (24th July 2013) - Jensen, Kristine Helander; Dargis, Rimtas; Christensen, Jens Jørgen; Kemp, Michael
<x xml:space="preserve">Abstract</x> The use of broad range PCR and DNA sequencing of bacterial 16S ribosomal RNA genes for routine diagnostics of bacterial infections was evaluated. Here, the results from more than 2600 analyses during a 6‐year period (2003–2009) are presented. Almost half of the samples were from joints and bones, and the second most frequent origin of samples was from the central nervous system. Overall, 26% of all samples were positive for bacterial DNA and bacterial identification was obtained in 80% of the PCR‐positive samples by subsequent DNA sequencing. Ambiguous species identification was noticed among non‐haemolytic streptococci, especially within the mitis group. The data show that ribosomal PCR with subsequent DNA sequencing of the PCR product is a most valuable supplement to culture for identifying bacterial agents of both acute and prolonged infections. However, some bacteria, including non‐haemolytic streptococci, may not be precisely identified.